The Effect of Attention Focus ofInstruction on Novices' Skill LearningBased on Newell's Learning StagesModel - Hamed Abdolmaleki; Bahram Ghafari (University of Tehran, 2016)
Newell's learning stages model is a learning model based on dynamic systems theory which is divided to three stages based on the relationship among learners' degree of freedom. The aim of this study was to investigate the effect of attention focus of instruction on learning a simple skill (throwing darts) and a complex skill (non-dominant foot chip shot). Thestudyconsistedoftwoexperiments. In thefirst experiment,24male studentsofUniversity of Tehran were instructed tothrow darts. Participantsweredivided into two groupsbased onpretest scores, and thenone group received internalfocusinstructionsand the otherexternalfocus instruction. Results showed that external attention focus was more beneficial when learning the skill of throwing darts. In the second experiment, 24 male students of University of Tehranwere instructedto perform non-dominant foot chip shot skill. Participants were divided into two groups based on their pretest scores, and thenone groupreceived internalattention focusinstructionsand otherexternalfocus instruction. The results showed that internal focus of attention was more beneficial when learning the non-dominant foot chip shot. Results of this study suggested that it was more useful to adopt an internal focusin skills whose coordinative structures have not yet formed.